In Situ Activating Ubiquitous Rust towards Low‐Cost, Efficient, Free‐Standing, and Recoverable Oxygen Evolution Electrodes. Issue 34 (20th July 2016) - Zhong, Haixia; Wang, Jun; Meng, Fanlu; Zhang, Xinbo
Abstract: Developing effective ways to recycle rusted stainless steel and to promote the sluggish oxygen evolution reaction (OER), associated with water splitting and metal–air batteries, is important for a resource‐sustainable and environment‐friendly society. Herein, we propose a strategy to enable rusted stainless steel plate to be used as an abundant and low‐cost OER catalyst, wherein a hydrothermal combined in situ electrochemical oxidation–reduction cycle (EORC) method is developed to mimic and expedite the corrosion process, and thus activate stainless steel into free‐standing OER electrodes. Benefiting from the plentiful electrolyte‐accessible Fe/(Ni) oxyhydroxides, high conductivity and mechanical stability, this electrode exhibits remarkable OER performances including low overpotential, fast kinetics, and long‐term durability. The slight degradation in current after long‐term use can be repaired immediately in situ by an EORC. Abstract : To turn waste into treasure, rusty stainless steel is recycled into low‐cost, efficient, free‐standing oxygen evolution reaction (OER) electrodes via an electrochemical oxidation–reduction cycle in an electrolyte.